FERGANA-TASHKENT ROUTES OF TASHKENT ROUTES ORIGIN. - Ilyos Mahmudov Ikromjon o’g’li (Research Focus International Scientific Journal, 2023)
In this article, the history of the formation of maqom, types of maqom, ways of singing and maqom with series and without series in the 19th-20th centuries in the Fergana Valley, the oasis taking the leading places in the heritage of classical music, local performance traditions, Fergana-Tashkent full information about the history of the origin of the song section of the status roads.